CAKTI ECONOMIC THEORY: National Income and State Welfare Improvement Strategy Online Software-based - Gunawan, Cakti Indra (International Research & Development for Human Beings (IRDH), 2024)
I thank God Almighty who gave His grace and blessings to this Cakti Economics Theory (CET): Modern Humanity Economic Theory. Without Him CET would not be invented. I would also like to thank my mother Sri Rejeki and my father Mino who always pray and encourage me. Thanks to Mino big family, Marsiyo Kartomartejo and Karso Prawiro who motivate me. For my son, Vega Raksa C. Cakti (Aksa), I thank you for your patience, prayers, and support. I hope you will always be devoted. My deepest gratitude to all teachers and lecturers who had taught me, without you it’s impossible to invent CET for human beings welfare. Especially for Prof. HMS Idrus, SE., Mec., Phd (Universitas Brawijaya), Prof Amarjit Kaur FASSA, and Zifirdaus Adnan, BA., MA., PhD (The University of New England, Australia) who guided me in making undergraduate thesis, thesis, and dissertation, thank you for all that you have taught me. To all fellow lecturers, researchers, and writers in Indonesia and overseas, for university undergraduate and postgraduate students, I thank you all, because without you CET will not be published globally. I also want to send biggest gratitude to all parties that could not be mentioned who always have and always will support CET. May God reward your kindness. My biggest hope is for CET to benefit the science development in 21st century globalization era, will survive for the next centuries, and last forever. I hope it will be advantageous for economic acceleration strategy and human resource improvement, to prevent poverty, unemployment, terrorism, separatism, corruption, and crime based on online report by citizens and state apparatuses connected from village to central government. May God give His blessing to all nation leaders in the world who would gain benefit from CET to achieve economic welfare and spiritual happiness in each country while at the same time also able to prevent civilization collapse by greed.